Meningkatkan Keterampilan Merangkai Bunga Mawar Dari Manik Akrilik Menggunakan Video Tutorial Bagi Anak Tunagrahita Ringan - Hutda, Mifta; Taufan, Johandri (Jurnal Penelitian Pendidikan Khusus, 2022)
The purpose of this study was to improve the skill of arranging roses from acrylic beads through video tutorials for two mild mentally retarded children in SLB Negeri 1 Bukittinggi clss VI. This type of research is classroom action research which is carried out in two cycles. Cycle I consisted of four meetings and cycle II consisted of four meetings. The stages of each cycle are planning, action, observation and reflection stages. The results showed that there was an increase in children’s ability to arrange roses from acrylic beads. Percentage of initial ability AK 29,03%. In the first cycle it increased to 54,83% and the second cycle 80,64%. Meanwhile in DM children, the initial condition was 32,25%. In the first cycle there was an increase of 64,51% and the second cycle to 87,09%. The conclusion is that video tutorials can improve the skills of arranging roses from acrylic beads for grade VI mild mentally retaeded children at SLB Negeri 1 Bukittinggi.